CONDITIONS AND FACTORS FOR DEVELOPING LOGICAL THINKING IN PRESCHOOL CHILDREN - Sharofiddinova Ra’noxon; Xolmatova Yodgoroy (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This topic analyzes the main conditions and factors of the development of logical thinking in preschool children (3–7 years old) from a scientific and pedagogical point of view. The study studies the role of logical thinking in the psyche of children, social, family and pedagogical factors influencing its development. The possibilities of forming logical thinking in preschool educational institutions through the use of didactic games, experimental training and problem situations are shown. The results of the study are presented in the form of practical recommendations for preschool educators.